Conceptualizing Agile Branding: Dimensions and Antecedents for Managing Brands in a Dynamic Environment. - Pöhlmann, Michaela; Seitz, Jürgen; Jambrino-Maldonado, Carmen; De-las-Heras-Pedrosa, Carlos (MDPI, 2024)
Traditional branding approaches take too long to react to today’s dynamic environment. Agile branding offers a promising approach and might be the contemporary answer to the demands of our digitalized world. While scientists state that an agile approach to branding is essential nowadays, there is a lack of knowledge on how agile branding can be conceptualized and applied in practice. This article aims to provide a better understanding of agile branding by identifying its dimensions and antecedents. This study pursued a multi-method approach: a systematic literature review was conducted, followed by qualitative semi-structured interviews with eleven experts and a group discussion with five participants. Applying the dynamic capabilities perspective, the authors identify five dimensions, including 20 antecedents of agile branding: (a) leadership style and culture, (b) employee skills and competencies, (c) technology and methods, (d) stakeholder and feedback integration, and (e) ambidexterity. The critical challenge of agile branding is to balance brand continuity and adaptation. The study is the first to conceptualize agile branding, offering scientists and practitioners values and principles on how brands can be managed and further evolved in a constantly changing world to stay relevant in the market and ahead of the competition.
Keywords: Aprendizaje conceptual - Marketing; Gestión de marketing; Marcas (Marketing) - Estudio de casos; Agile branding; Agility; Strategic brand management; Brand management